PENGARUH METODE GAMIFIKASI BERBANTUAN KAHOOT TERHADAP KETERAMPILAN MEMBACA SISWA KELAS III PADA MATA PELAJARAN BAHASA INDONESIA DI SD - Sandrina Dwi Melany; Ahmad Syarif; Desy Rosmalinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of gamification method assisted by Kahoot on the reading comprehension skills of third-grade elementary school students in Bahasa Indonesia subject. The study employed a quantitative approach with a quasi-experimental design using a Pretest-Posttest Control Group Design. Subjects consisted of 42 students from SDN 100 Muara Bungo, divided into an experimental class (Class III C, n=21) and a control class (Class III A, n=21). The experimental class received gamification-based learning using Kahoot, while the control class used conventional methods. Data were collected through reading comprehension tests covering three indicators: finding explicit and implicit information, identifying story elements (characters, setting, events), and drawing conclusions. Validity was tested using Pearson Product Moment correlation, and reliability using Cronbach’s Alpha (α = 0.746). Data analysis included normality test (Shapiro-Wilk), homogeneity test (Levene’s Test), Independent Sample t-test, and N-Gain test. Results showed that the experimental class achieved a posttest mean of 81.10, significantly higher than the control class mean of 71.67. The Independent Sample t-test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between groups. The N-Gain score for the experimental class was 0.46 (medium category), compared to 0.18 (low category) for the control class. The study concludes that the gamification method assisted by Kahoot has a significant positive effect on the reading comprehension skills of third-grade elementary students.